Букварь - Федотов Гавриил Федотович (Удмурт книжной издательство, 1962)
Экземпляры: УКП (20230401) / Инвентарный номер: АП19620107 / Сис.шифр: 81.664.1 / Авт.знак: Ф 34 / ГРНТИ: 16.41.25 / ББК: 81.664.1-92/-97